2019
DOI: 10.1039/c9ob00558g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of antiproliferative microtubule-destabilising combretastatin A-4 piperazine conjugates

Abstract: We report novel cis-restricted combretastatin A-4 analogues with potent antiproliferative effects in breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…All synthesized analogs were tested against MCF-7 cells. Two amino-containing derivatives 4q, 4x and hydroxyl derivative 4m exhibited strong activity with 130 nM, 83 nM and 190 nM IC 50 values, respectively [68].…”
Section: Antiproliferative Activitymentioning
confidence: 98%
“…All synthesized analogs were tested against MCF-7 cells. Two amino-containing derivatives 4q, 4x and hydroxyl derivative 4m exhibited strong activity with 130 nM, 83 nM and 190 nM IC 50 values, respectively [68].…”
Section: Antiproliferative Activitymentioning
confidence: 98%
“…Derivative 43 revealed an IC 50 value of 83 nM against MCF-7 breast cancer cells, unfortunately, the activity of 43 is not as high as the lead compound combretastatin-A4 (IC 50 ¼ 3.9 nM). Furthermore, compound 43 was selectively toxic to MCF cells, inducing G2/M phase arrest and apoptosis of MCF-7 cells, but not in peripheral blood monocytes, and inducing cleavage of DNA repair enzyme poly adenosine diphosphate ribose polymerase (PARP) in MCF-7 cells 68 . Singh et al reported the synthesis and anticancer activities of colchicine derivatives.…”
Section: Biological Effects Of Natural Products Containing the Piperazinyl Moietymentioning
confidence: 99%
“…Docking studies indicate that the trimethoxy A rings overlay with with those of DAMA-colchicine, whilst the B ring of the piperazine conjugates align with the the C ring of DAMA-colchicine. Toxicity of the compounds is minimal and water-soluble conjugates will be developed for the potential treatment of triple-negative breast cancer [101].…”
Section: Piperazine Conjugatesmentioning
confidence: 99%